Differential and Synergistic Functionality of Acylsugars in Suppressing Oviposition by Insect Herbivores. - Brian M Leckie; Damon A D'Ambrosio; Thomas M Chappell; Rayko Halitschke; Darlene M De Jong; André Kessler; George G Kennedy; Martha A Mutschler (PLoS ONE, 2016)
Acylsugars are secondary metabolites exuded from type IV glandular trichomes that provide broad-spectrum insect suppression for Solanum pennellii Correll, a wild relative of cultivated tomato. Acylsugars produced by different S. pennellii accessions vary by sugar moieties (glucose or sucrose) and fatty acid side chains (lengths and branching patterns). Our objective was to determine which acylsugar compositions more effectively suppressed oviposition of the whitefly Bemisia tabaci (Gennadius) (Middle East--Asia Minor 1 Group), tobacco thrips, Frankliniella fusca (Hinds), and western flower thrips, Frankliniella occidentalis (Pergande). We extracted and characterized acylsugars from four S. pennellii accessions with different compositions, as well as from an acylsugar-producing tomato breeding line. We also fractionated the acylsugars of one S. pennellii accession to examine the effects of its components. Effects of acylsugars on oviposition were evaluated by administering a range of doses to oviposition sites of adult whiteflies and thrips in non-choice and choice bioassays, respectively. The acylsugars from S. pennellii accessions and the tomato breeding line demonstrated differential functionality in their ability to alter the distribution of whitefly oviposition and suppress oviposition on acylsugar treated substrates. Tobacco thrips were sensitive to all compositions while western flower thrips and whiteflies were more sensitive to acylsugars from a subset of S. pennellii accessions. It follows that acylsugars could thus mediate plant-enemy interactions in such a way as to affect evolution of host specialization, resistance specificity, and potentially host differentiation or local adaptation. The acylsugars from S. pennellii LA1376 were separated by polarity into two fractions that differed sharply for their sugar moieties and fatty acid side chains. These fractions had different efficacies, with neither having activity approaching that of the original exudate. When these two fractions were recombined, the effect on both whiteflies and thrips exceeded the sum of the two fractions' effects, and was similar to that of the original exudate. These results suggest that increasing diversity of components within a mixture may increase suppression through synergistic interactions. This study demonstrates the potential for composition-specific deployment of acylsugars for herbivore oviposition suppression, either through in planta production by tomato lines, or as biocides applied by a foliar spray.